A Survey on Metasurface-Based Antennas for CubeSat Spacecrafts - Boutaina Benhmimou; Fouad Omari; Nancy Gupta; Khalid El Khadiri; Rachid Ahl Laamara; Mohamed El Bakkali (Majlesi Journal of Electrical Engineering, 2025)
The Present CubeSat project success rate may deter nonprofit organizations from beginning new projects, especially for first-time creators. However, since the electronic components of a CubeSat are intended to be very power-efficient and tightly placed, its size and electrical characteristics provide a more difficult limitation. The CubeSat antennas are key parts that will need to be carefully designed since they need to be tiny, light, and deployable for bigger antennas. This study provides an extensive overview of the key characteristics of metasurface-based antennas with an emphasis on their effectiveness in CubeSat communication systems. This research work initially introduces metasurface antennas and examines how well-suited they are geometrically for various frequency bands for CubeSat spacecraft. Furthermore, a detailed analysis of these metasurface antennas’ radiating capabilities is conducted in accordance with the CubeSat configuration, links, and orbits. Additionally, over thirty X-band metasurface-based antennas are fully evaluated in terms of their suitability for CubeSats. The use of specifically designed metasurfaces has resulted in a notable increase in CubeSat antenna performance. This paper offers an emerging approach for researchers to advance the usage of metasurface-based antennas in CubeSat missions such as UM5-Ribat and UM5-EOSAT CubeSats of University Mohammed V in Rabat.